The evaluation of the local beer industry during the COVID-19 pandemic and its relationship with open innovation - Ardvin Kester S. Ong; Arianne R. Peque\~na; Yogi Tri Prasetyo; Thanatorn Chuenyindee; Thapanat Buaphiban; Satria Fadil Persada; Reny Nadlifatin (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The beer industry is one of the businesses affected during the COVID-19 pandemic. Despite the exponential growth of the beer industry throughout the years, this aspect of the beverage industry has gained limited attention and has been underexplored. This study aimed to provide a better and up-to-date understanding of Philippine-beer consumers to speed up its recovery. An online survey with 853 volunteer respondents was conducted to investigate Filipinos' local beer consumption considering frequency, intake, expenses, and preference. A descriptive analysis of the consumers' self-perceived evaluation of the changes in drinking showed a slight decrease in frequency, intake, and expenses and a minor change in preference. Somers' d and the chi-squared test results indicated significant relationships between each demographic information (age, sex, and income) and frequency, intake, and expenses. In addition, a conjoint analysis with an orthogonal design indicated that price was the most important attribute (58.025%), followed by primary taste (12.452%), alcohol content (9.706%), mouthfeel (6.445%), aftertaste (6.355%), aroma (5.189%), and, lastly, color (1.827%). The findings of this study could be used as a baseline for improved product offerings, customized advertisements, and market segmentation. Moreover, the results of this study could be applied and extended by breweries to promote and create strategies. Lastly, this study could be extended and utilized by other beverage industries worldwide.
Keywords: 650; COVID-19 pandemic; beer; conjoint analysis; consumer preference; expenditure